The Land is The Icon: Disappearing Architecture on Natural Force - Bramasta Putra Redyantanu (Advances in Civil Engineering and Sustainable Architecture, 2025)
This paper reimagines architectural landmarks within the hills of Labuan Bajo, proposing an approach where architecture seamlessly integrates with the landscape rather than asserting dominance. The study examines how design strategies can amplify rather than overshadow the natural environment, positioning nature as the true landmark through ephemeral architecture. Using Plowright’s force-based framework within an architectural competition, the research employs a research-by-design methodology to iteratively refine solutions that dissolve built interventions into the terrain. By integrating Labuan Bajo’s topographical and visual characteristics, the design leverages adaptive modularity and sustainable strategies to ensure perceptual fluidity within the site’s ecological and cultural context. This approach contributes to landmark design by demonstrating how architecture can function as a dynamic extension of the landscape, fostering harmony rather than visual competition.